A comparative evaluation of microleakage and compressive strength of Ketac Molar, Giomer, Zirconomer, and Ceram-x: An in vitro study - Rashmeet Walia; Purshottam Jasuja; Kanika Gupta Verma; Suruchi Juneja; Aditi Mathur; Lovejeet Ahuja (Wolters Kluwer Medknow Publications, 2016)
Background: Microleakage around dental restorative material and strength to withstand the masticatory forces is major problem in dentistry. Instead, many new materials available, very few actually bond to tooth surface and bear masticatory load. Aim: The aim of this study is to evaluate and compare the microleakage and compressive strength of Ketac Molar, Giomer, Zirconomer, and Ceram-x. Materials and Methods: For the evaluation of microleakage, Class V cavities were prepared on sixty human premolar teeth and divided into four study groups (n = 15): Group I (Ketac Molar), Group II (Giomer), Group III (Zirconomer), and Group IV (Ceram-x). The samples were thermocycled and subjected to dye penetration test. The sections were made and evaluated under stereomicroscope at × 40 magnification. For the compressive strength evaluation, sixty cylindrical specimens were fabricated measuring 5 mm × 6 mm and grouped into four study groups (n = 15): Group I (Ketac Molar), Group II (Giomer), Group III (Zirconomer), and Group IV (Ceram-x). All were then subjected to the Universal Testing Machine at crosshead speed of 1 mm/s. Statistical Analysis Used: The data were analyzed using paired t-test and ANOVA. Results: The microleakage was found insignificant (P > 0.05) for all study groups, with Giomer showing maximum followed by Zirconomer, Ceram-x, and Ketac Molar. The compressive strength was found to be highly significant (P < 0.01) with the maximum score for Giomer followed by Ceram-x, Zirconomer, and Ketac Molar. Conclusion: The sealing ability was maximum in Ketac Molar, Zirconomer, Ceram-x, and Giomer whereas the compressive strength was maximum for Giomer followed by Ceram-x, Zirconomer, and Ketac Molar.